Precast concrete : materials, manufacture, properties and usage - Levitt, M. (Taylor & Francis, 2008)
This general treatise on precast concrete reflects Maurice Levitt's extensive experience in the construction industry and as a researcher and consultant. It gives detailed coverage of the subject from the material's properties through its manufacture and quality control, and on to specialist topics such as accelerated curing and use in hot and cold climates.
1st ed. published: London; Englewood, N.J. : Applied Science Publishers Ltd., ©1982.
Keywords: Precast concrete.; elektronické knihy; electronic books